PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA BANK MANDIRI SYARIAH BANGKINANG - Yudi Syaputra; Arman Arman (Jurnal Riset Manajemen Indonesia, 2020)
This study aims to determine the effect of competence and work environment on employee performance at Bank Mandiri Syariah Bangkinang. The analysis used as many as 34 people. The research approach used is quantitative with multiple linear regression analysis models. The technique of data collection is done by observing directly on the object of research and giving questionnaires to employees of Bank Mandiri Syariah Bangkinang. From the results of the analysis it can be concluded that, there is a significant simultaneous and partial variable effect between competence and work environment on employee performance at Bank Mandiri Syariah Bangkinang. Hypothesis testing is done by the F test and t test, based on simultaneous testing (together) and partial testing (individual). Competence and work environment affect the performance of Bank Mandiri Syariah Bangkinang.